FUND MANAGEMENT STRATEGY IN BAZNAS ZAKAT (AMIL ZAKAT NATIONAL AGENCY) EAST JAVA - Widiastuti, Tika; Wahyuningsih, Wahyuningsih; Indrawan, Imam Wahyudi (IJIBE (International Journal of Islamic Business Ethics), 2016)
Poor people in the world remains a global problem. Previous studies have been widely using various perspectives related to aspects of fundamental and macroeconomic. However, research that focuses on methods to manage zakat institutions still do not exist. Especially on zakat management institutions in Indonesia. Countries with a Muslim majority population in the world. This study used a qualitative approach through multiple cases study aimed to determine the zakat fund management strategies at the National Zakat Agency and the Institute of National Zakat Al Ahzar East Java. Data collected through individual depth interview. This study describes the findings of Zakat Scorecard Model through categorical analysis results. The article also describes the academic and managerial implications related to zakat management institutions.